PROVISION OF PUBLIC SERVICES IN THE ADMINISTRATIVE LEGAL SYSTEM OF THE REPUBLIC OF SERBIA (Heritage, 2024)
The provision of public services is a legal institute that is applied in the legal system of the Republic of Serbia for the purpose of realizing rights and legal interests in the context of exercising the general interest, and at the same time represents one of the administrative matters provided for by the Law on General Administrative Procedure. The provision of public services, as a legal institute, is introduced into the administrative legal system of the Republic of Serbia by the adoption of the Law on General Administrative Procedure ("Official Gazette of the RS", No. 18/2016 and 2/2023 - Decision of the US RS. See: Authentic interpretation - 95/2018 ), and in accordance with the tendency of harmonizing our legislation with the legal system of the European Union. This institute is regulated by the aforementioned law (Articles 31 and 32), through two articles. Its introduction into the administrative legal system shows the seriousness of the work of the public administration, and thus enables a safer and more favorable position of the parties in terms of meeting the needs of users of public services. Bearing in mind that the provision of public services represents a novelty in administrative procedures, especially through the system of introduction of E-administration, the effects of the application of this institute in practice will be the subject of consideration in order to further improve its normative framework. Public administration reform represents one of the key processes of European integration, which at the same time represents a process that should improve the entire system of public administration in the Republic of Serbia, and therefore the quality of services that public administration provides to users of public services.
Keywords: provision of public services, Law on General Administrative Procedure, concept, purpose, E-administration, protection, complaint, citizen's protector, trustee, comparative legal system, European Union